2018
DOI: 10.1016/j.ijpara.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the differences: comparative proteomic analysis of a clonal virulent and an attenuated Histomonas meleagridis strain

Abstract: The current study focused on Histomonas meleagridis, a unicellular protozoan, responsible for histomonosis in poultry. Recently, the occurrence of the disease increased due to the ban of effective chemotherapeutic drugs. Basic questions regarding the molecular biology, virulence mechanisms or even life cycle of the flagellate are still puzzling. In order to address some of these issues, we conducted a comparative proteomic analysis of a virulent and an attenuated H. meleagridis strain traced back to a single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
4
15
0
Order By: Relevance
“…Despite substantial differences between 2-DE and 2D-DIGE, such as in the experimental design, the applied amount of protein, influence of technical variation and protein spot detection, the protein patterns obtained by the two techniques showed a high level of similarity. The observed distribution of protein spots in the 2D-DIGE-α and 2D-DIGE-β experiments was in agreement with previously published conventional 2-DE gels of H. meleagridis cultures (Monoyios et al, 2018 ). In the conventional 2-DE study as well as in the 2D-DIGE, a noticeable difference in the M r distribution of proteins between virulent and attenuated culture samples was revealed (Monoyios et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite substantial differences between 2-DE and 2D-DIGE, such as in the experimental design, the applied amount of protein, influence of technical variation and protein spot detection, the protein patterns obtained by the two techniques showed a high level of similarity. The observed distribution of protein spots in the 2D-DIGE-α and 2D-DIGE-β experiments was in agreement with previously published conventional 2-DE gels of H. meleagridis cultures (Monoyios et al, 2018 ). In the conventional 2-DE study as well as in the 2D-DIGE, a noticeable difference in the M r distribution of proteins between virulent and attenuated culture samples was revealed (Monoyios et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Protein spots were distributed within a pH range of 5–7 and a M r of 15–140 kDa (Figures S3, S4). The landmark spot, which was distinctive at pI 5 and a M r of ~50 kDa (Figures S3, S4), was known to be actin of H. meleagridis origin based upon a previous study (Monoyios et al, 2018 ). The visualization of this actin spot with yellow color was an indication that it was not differentially expressed between the in vitro cultivated virulent and attenuated parasites (Figure S3 ).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, the study elucidated potential pathogenic mechanisms in respect to cytoadherence and host cell membrane disruption, together with the possible regulation of such processes. Monoyios et al ( 41 ) addressed differences between in vivo cultivated virulent and attenuated H. meleagridis parasites on protein expression level. Based on mass spectrometry data it could be shown that eight different proteins, with the majority related to cellular stress management, have been found up-regulated in virulent histomonads compared to the attenuated strain which potentially affect the host-pathogen interaction between the two strains.…”
Section: Introductionmentioning
confidence: 99%